Designing of playground by children and their opinion on play - Korkmaz, Nimet Haşil (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Project aims to develop disabled and abled children’s sense of awareness about their city by having them participate in decision processes in urban settlement areas and form an ability for designing urban areas according to disabled and abled children. During the project, training and practical works are done to get a playground where disabled and abled children can play together. Material and Methods. 24 abled and 6 disabled elementary school students are trained. Total of 27 students, 22 abled and 5 disabled, were administered the questionnaire. The opinions of the students about the play were taken through the questionnaire and the semi-structured interview method. Results. 80% of the disabled students answered that they spared 3-4 hours’ and 50% of the abled students spared 0-2 hours’ to playing. 60% of the disabled students and 55% of the abled students play games with their families. 80% of the disabled students did not play games. 50%of the abled students play games during break times at school. 60% of the disabled students did not play games in the street. 55% of the abled students play games in the street. It is observed that 80% of the disabled and 59% of the abled students who participated in the study did not play in the playgrounds in their neighborhoods. 80% of the disabled students considered that 1-3 hours of playing would be enough. 82% of the abled students considered that 2-4 hours of playing would be enough. Conclusions. Disabled and abled children design the playground where they would be able to play together. Children were made to acquire a sense of awareness both about their city and laying claim to their playing rights. It was determined that playing times of children should be expanded and playgrounds increasing their power of imagination are needed
Keywords: play; disabled; abled; playground